Analysis of Communication Barriers in the Muslimat Mathla’ul Anwar Organization - Yulie Hanna Harmaini; Suwardi Lubis; Dewi Kurniawati (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study investigates internal communication barriers within Muslimat Mathla’ul Anwar (MUSMA) North Sumatra, an Islamic women’s organization devoted to da’wah, education, and social empowerment. The research employs a qualitative case study design, using in-depth interviews and direct observations, with data analyzed using the Miles and Huberman interactive model, supported by triangulation. Findings reveal four dominant barriers: vertical communication dominated by top-down information flow; psychological tension reflected in weak emotional bonds; technological limitations marked by low digital literacy and minimal platform optimization; time constraints shaped by members’ external responsibilities and generational differences. These conditions reduce coordination, participation, and organizational responsiveness. The study highlights the need for adaptive, participatory, and empathetic communication practices, strengthened by improved digital literacy and structured feedback mechanisms. The research contributes to organizational communication theory by showing that seniority-based cultural norms in women’s religious organizations intensify technological and structural barriers, requiring communication reforms grounded in socio-cultural rather than purely technical approaches.